“We Care, We Share, We Concern”: a qualitative study of a youth leadership development program - Ahmad, Mohamad Firdaus; Safwan, Nur Syazwani Zulaikha; Dahlan, Nur Dalilah (Universiti Teknologi MARA, Kedah, 2024)
This paper aims at providing a qualitative study of the “WE CARE, WE SHARE, WE CONCERN” program, which is a leadership development program for adolescents in secondary school in Malaysia. This research uses Participatory Action Research and Contextual Inquiry methods to assess the facilitators’ views from the Diploma in Sports and Recreation Management program in UiTM. The sources of data used in this study include observations made by the facilitators, ongoing discussions and analysis, and reflective journals. Implications of the study include the identification of the program’s findings, positive changes in behavioral patterns among participants, and barriers encountered in the field. Therefore, the outcomes of the present study indicate that this approach is beneficial for advancing knowledge on the effects of leadership programmes for youths as well as for designing and evaluating such programmes.